Application of the Problem Based Learning Model ( PBL ) To Improve Critical Thinking Skills and Mastery of Concepts on Environmental Pollution Materials - Damis Dewi Sundani (Universitas Pakuan, 2021)
The Problem Based Learning Model (PBL) is a learning model that is highly recommended in the implementation of the National Curriculum. This research is to obtain an overview of the implementation of PBL in learning environmental pollution in an effort to improve critical thinking skills and mastery of concepts. This research was carried out by the quasi-experimental method, namely the pretes-postes control design. The study subjects were 73 students who were divided into control groups and experimental groups. The data obtained comes from the completion of the critical thinking test problem in the form of a description and mastery of the concept in the form of multiple choices. The results of the study explain that the acquisition of critical thinking skills with higher value PBL learning ( average - = 82.1) compared with conventional learning ( average - =61.4 ) with a calculated t value of 28.34 (p 0.05). Mastery of concepts with PBL learning gets a higher score ( average - average = 76) compared to conventional learning ( average - 0.05TAG. The results showed that the PBL learning model was able to improve critical thinking and mastery of the concept of students in class X environmental pollution material at Senior High School 1 Dramaga.